The Role of Semipurified Fractions Isolated from Quercus infectoria on Bone Metabolism by Using hFOB 1.19 Human Fetal Osteoblast Cell Model - Amira Raudhah Abdullah; Hermizi Hapidin; Hasmah Abdullah (Hindawi, 2024)
Background. Quercus infectoria (QI) is a plant used in traditional medicines in Asia. The plant was reported to contain various active phytochemical compounds that have potential to stimulate bone formation. However, the precise mechanism of the stimulation effect of QI on osteoblast has not been elucidated. The present study was carried out to isolate QI semipurified fractions from aqueous QI extract and to delineate the molecular mechanism of QI semipurified fraction that enhanced bone formation by using hFOB1.19 human fetal osteoblast cell model. Methods. Isolation of QI semipurified fractions was established by means of column chromatography and thin layer chromatography. Established QI semipurified fractions were identified using Liquid Chromatography-Mass Spectrometry (LC-MS). Cells were treated with derived QI semipurified fractions and investigated for mineralization deposition and protein expression level of BMP-2, Runx2, and OPN by ELISA followed gene expression analysis of BMP-2 and Runx2 by RT-PCR. Results. Column chromatography isolation and purification yield Fractions A, B, and C. LC-MS analysis reveals the presence of polyphenols in each fraction. Results show that QI semipurified fractions increased the activity and upregulated the gene expression of BMP-2 and Runx2 at day 1, day 3, and day 7. OPN activity increased in cells treated with QI semipurified fractions at day 1 and day 3. Meanwhile, at day 7, expression of OPN decreased in activity. Furthermore, the study showed that combination of Fractions A, B, and C with osteoporotic drug (pamidronate) further increased the activity and upregulated the gene expression of BMP-2 and Runx2. Conclusions. These findings demonstrated that polyphenols from semipurified fractions of QI enhanced bone formation through expression of the investigated bone-related marker that is its potential role when combined with readily available osteoporotic drug.